Removal efficiency of a fast setting pozzalan-based bioactive cement: a micro CT study - Feyza Çetinkaya; Ahter Şanal Çıkman; Ali Keleş; Banu Arıcıoğlu (BMC, 2024)
Abstract Aim The aim of this study was to evaluate the removal efficiency of PRMTA and ECMPremixed applied to the coronal third according to the RET by UI and to examine the effect of different solutions on material removal. Materials and methods 40 permanent upper central teeth were used to simulate immature teeth. The samples were irrigated with 1.5% NaOCl and calcium hydroxide was placed. Samples were incubated in PBS. Then irrigation was done with 17% EDTA, the samples were randomly divided into 2 groups (n = 20):Group 1: PRMTA, Group 2: ECM Premixed. The materials were placed in the samples. Then the samples were scanned with micro-CT. Materials were removed by UI. Micro-CT scan of the samples was performed. Each material group was divided into 2 subgroups (n = 10): Group1 was MTAD, group2 was irrigated with 10% CA; then micro-CT was performed. Obtained images were positioned in DataViewer and analyzed with CTAn. The obtained data were statistically analyzed in IBM SPSS 25. The significance level was determined as 5%. Results There was no significant difference between the initial volumes of the materials (p > 0.05). The amount of the remaining material after UI was significantly higher in the PRMTA (0.7471%) group compared to the ECM Premixed (0.0093%). There was no significant difference in terms of remaining material after irrigation with MTAD and CA in both groups (p > 0.05). Conclusion A great deal of the materials were removed by UI under the operation microscope. ECM Premixed was removed more effectively compared to the PRMTA. And, acidic solutions did not provide any additional benefit in material removal.